Deliver us from evil the slavery question in the old south - Ford, Lacy K. (Oxford University Press, 2009)
Illuminates the white South's efforts to justify slavery, focusing on the period from the drafting of the federal constitution in 1787 through the age of Jackson. Draws heavily on primary sources, including newspapers, government documents, legislative records, pamphlets, and speeches.